ANALISIS TENTANG NILAI-NILAI MORAL DALAM TRADISI MANDI SAMPAT PADA UPACARA PERKAWINAN MASYARAKAT MELAYU DI KELURAHAN TEBING KECAMATAN TEBING KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Ardhiansyah, Tri; Arianto, Jumili; ', Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by one of the traditions in the Malay community marriage ceremony, which is usually called Mandi tradition Sampat. The existence of the tradition of bathing sampat are currently conducted in the marriage ceremony as a cornerstone value for society wearer. The problems in this study is whether there is a Moral Values in the tradition of the nuptial Mandi Sampat Malay community in the Village Of Tebing Sub District Karimun Province Of Kepulauan Riau?. The purpose of this study was to determine the Moral Values contained in Mandi Sampat tradition in wedding ceremonies Malay community. The population in this study is the whole community in the Village of tebing married as many as 1,383 families . In the opinion of Earl Babbie (Prijana, 2005), that in order to understand the samples that were relevant in qualitative research is "sampling is the process selecting" selection process intended to get people, situations, events / activities and documents obtained from the number of people who can express or documents / population then selected based on a lot of goals to be achieved and to select the appropriate issue. Based on the opinion of Earl Babbie that researchers are allowed to select the desired sample in harmony with the technique of sampling purposeive ie 60 people. Data were collected through observation, questionnaires, interviews, and technical literature. In analyzing the data using qualitative descriptive analysis.The results of this study indicate that there is a Moral Values in the tradition of Mandi Sampat the Malay community marriage ceremony in the village Of Tebing Sub District Karimun Province Of Kepulauan Riau. Judging from the results of 60 respondents saying percentage of (74.99%), and included in the benchmark "Yes" is between 50.01% -100%. So the hypothesis is accepted and proven that there is a Moral Values In Tradition Sampat Mandi In Marriage Ceremony Malay community in the Village Of Tebing Sub District Karimun Province Of Kepulauan Riau.Keywords: Moral Values, Traditions Mandi Sampat2